Peradeniya : memories of a university - De Silva, K. M.; Jayatilaka, Tissa; International Centre for Ethnic Studies (Kandy : International Centre for Ethnic Studies, 1997)
Collection of essays on undergraduate life at the University of Peradeniya.
Keywords: University of Peradeniya -- History; University of Peradeniya -- Students -- History